C-reactive protein testing to guide antibiotic prescribing for COPD exacerbations: A protocol for systematic review and meta-analysis. Issue 29 (17th July 2020) - An, Xing; Zhang, Chuantao; Weng, Xiangwen; Xiao, Wei; Sun, Zengtao; Zeng, Zhu; Huang, Qingsong
Abstract: Background: The use of antibiotics in the acute exacerbations of chronic obstructive pulmonary disease (COPD) remains controversial. Serum C-reactive protein (CRP), a sensitive biomarker for systemic inflammation and tissue damage, is a good indicator of lower respiratory tract bacterial infection. However, due to the small sample size of the existing studies, the clinical value of CRP in guiding the use of acute exacerbation of chronic obstructive pulmonary disease (AECOPD) antibiotics is insufficient. The aim of this study was to evaluate the value of CRP-guided treatment strategies for AECOPD patients. Methods: This review summarizes and meta-analyses randomized controlled trials (RCTs) of CRP guiding antibiotic prescribing for COPD exacerbations. RCTs compare either usual-care or the GOLD strategy have been included. The following electronic databases have been searched: PubMed, Cochrane Library, Embase, CNKI, CBM, VIP, and Wanfang Data. The methodologic quality of RCTs has been assessed using the Cochrane risk assessment tool. All trials included are analyzed according to the criteria of the Cochrane Handbook. Review Manager 5.3, R-3.5.1 software, and GRADE pro GDT web solution are used for data synthesis and analysis. Results: This review evaluates the effects of CRP testing on the antibiotic use, CCQ, EQ-5D utility scores and adverse events in patients with COPD exacerbations. Conclusion: This review provides clear evidence that CRP testing can reduce the use of antibiotics in patients with AECOPD without causing harm.